Canada-India row: a test of the “rules-based order” - Suryanarayana, P. S. (2023)
The United States is trying to control the storm arising from Canada’s implicit accusation that India committed an act of state-sponsored terrorism on Canadian territory. Under US auspices, Ottawa is seeking Delhi’s cooperation to investigate the murder of an India-born Canadian whom Delhi had designated as a terrorist responsible for fomenting separatism in India. At stake in this unfolding episode are Canada’s assertion of sovereignty and India’s rejection of the allegation that it sponsors terrorism. Both of these are aspects of the US campaign for a rules-based international order.